Socio-ecological Factors Associated with Adolescents’ Psychological Well-being: A multilevel analysis - Yuqi Guo; Laura M. Hopson; Fan Yang (International Journal of School Social Work, 2018)
Purpose: Supports and stressors across different ecological systems affect adolescents’ perceptions of psychological well-being. The purpose of this study is to analyze how social support, school experiences, and socio-economic factors relate to psychological well-being among adolescents. Furthermore, our study explores how family income shapes the relationship between social supports and well-being. Method: Multilevel linear regression models were applied to a sample of 19,767 middle and high school students, with students serving as Level 1 and schools as Level 2. Results: Students reporting more support from parents, friends, teachers, and neighbors and better school engagement perceive better psychological well-being. Furthermore, family income moderates the relationship between teacher support and adolescents’ psychological well-being. Implications for social work practice are discussed. Conclusion: Social support plays an important role in promoting adolescents’ psychological well-being. Teacher support is associated with better psychological well-being for all students, and this relationship is strongest for students from higher income families.
Keywords: adolescents; psychological well-being; social support; school engagement